Food quality 4.0: From traditional approaches to digitalized automated analysis. (January 2023) - Hassoun, Abdo; Jagtap, Sandeep; Garcia-Garcia, Guillermo; Trollman, Hana; Pateiro, Mirian; Lorenzo, José M.; Trif, Monica; Rusu, Alexandru Vasile; Aadil, Rana Muhammad; Šimat, Vida; Cropotova, Janna; Câmara, José S.
Abstract: Food quality has recently received considerable attention from governments, researchers, and consumers due to the increasing demand for healthier and more nutritious food products. Traditionally, food quality is determined using a range of destructive and time-consuming approaches with modest analytical performance, underscoring the urgent need to develop novel analytical techniques. The Fourth Industrial Revolution (called Industry 4.0) is progressing exponentially, driven by the advent of a range of digital technologies and other innovative technological advances. "Food Quality 4.0" is a new concept referring to the use of Industry 4.0 technologies in food analysis to achieve rapid, reliable, and objective assessment of food quality. In this review, we will first discuss the fundamentals and principles of Food Industry 4.0 technologies and their connections with the Food Quality 4.0 concept. Then, the most common techniques used to determine food quality will briefly be reviewed before highlighting the advancements made in analytical techniques to assess food quality in the era of Industry 4.0. Food Quality 4.0 is characterized by growing digitalization and automation of food analysis using the most advanced technologies in the food industry. Key aspects of Food Quality 4.0, including, among others, non-destructive fingerprinting techniques, omics technologies and bioinformatics tools, Artificial Intelligence and Big Data, have great potential to revolutionize food quality. Although most of these technologies are still under development, it is anticipated that future research will overcome current limitations for large-scale applications. Highlights: Consumer interest in food quality call for advanced and reliable analytical methods. Industry 4.0 has offered numerous opportunities in many fields, including food analysis. Food Quality 4.0 concept - determination of food quality using Industry 4.0 technologies. AI, Big Data, and smart sensors are important enablers of Food Quality 4.0 Innovations, digitalization, and automation experienced a massive boost.